Exploring Experiences Responding to the Individual Level Abortion Stigma Scale: Methodological Considerations From In-depth Interviews - Wollum, Alexandra; Makleff, Shelly; Baum, Sarah E. (Frontiers in Global Women's Health, 2021)
Background: The Individual-Level Abortion Stigma (ILAS) scale is a tool to measure multiple dimensions of stigma among people who have abortions. Despite use of the scale globally, little is known about participant experiences completing the scale. We assessed reactions to and experiences with the scale among women who obtained abortions in Mexico, exploring how the items made them feel about themselves and their abortion. Methods: We conducted 10 in-depth interviews with women approximately 6 months after their abortion. We explored experiences answering the ILAS overall as well as each sub-scale (self-judgement; worries about judgement; isolation; community condemnation). We used thematic analysis to examine overall experiences with the ILAS and framework analysis to summarize responses by sub-scale. Results: Many respondents reported positive experiences responding to the scale or said it served a therapeutic purpose. Other participants said the scale caused strong or mixed emotions or generated doubts. Women generally described mixed and negative reactions to the “worries about judgement” and “community condemnation” sub-scales, and more neutral or positive reactions to the “isolation” and “self judgement” sub-scales. Nearly all respondents hypothesized that completing the ILAS at the time of their abortion would be more difficult than responding months after their abortion. Conclusions: People can experience both positive and negative effects when responding to abortion stigma scales. Use of the scales may cause discomfort and introduce concepts that further perpetuate stigma. This study highlights the importance of carefully considering when it is appropriate to implement the scale and exploring safeguards for participants.